2005
DOI: 10.1007/s00280-005-0107-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of estrogen receptor β in breast cancer

Abstract: Ever since the estrogen receptor (ER) beta was discovered in 1996, we have been trying to determine its value as a prognostic and/or predictive factor in breast cancer and its potential as a novel target for pharmacological intervention. Recent progress in cellular experiments has shown that ERbeta works as counter partner of ERalpha through inhibition of the transactivating function of ERalpha by heterodimerization, distinct regulation on several specific promoters by ERalpha or ERbeta, and ERbeta-specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 36 publications
1
97
1
1
Order By: Relevance
“…Recent reports have shown that several natural peptides, including thyroid hormones, are able to inhibit cancer cell proliferation , Saji et al 2005, Vesely 2005, Yano et al 2006. In the present study, we have demonstrated that T 3 hormone exposure exerts an anti-proliferative effect on human ductal pancreatic adenocarcinoma cell growth, and that it is able to increase the effect of dFdCyd and DDP acting synergistically with them.…”
Section: Discussionsupporting
confidence: 63%
“…Recent reports have shown that several natural peptides, including thyroid hormones, are able to inhibit cancer cell proliferation , Saji et al 2005, Vesely 2005, Yano et al 2006. In the present study, we have demonstrated that T 3 hormone exposure exerts an anti-proliferative effect on human ductal pancreatic adenocarcinoma cell growth, and that it is able to increase the effect of dFdCyd and DDP acting synergistically with them.…”
Section: Discussionsupporting
confidence: 63%
“…The ratio ERa : ER-b within tumour cells has been hypothesised to play a functional role in cell growth (Shaw et al, 2006). Conflicting data have been reported on the role of ER-b either in vitro and in vivo, in that results from preclinical and clinical studies have associated ER-b either positively (protein expression) or negatively (mRNA) with prognosis and response to endocrine treatment (Cappelletti et al, 2004;Saji et al, 2005). The results of our study, showing a significant upregulation of ER-b after treatment irrespective of clinical response, do not help to get further insight into this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we discuss data concerning ERb expression in human breast cancer in vivo and its relationship to clinical outcome in order to gain insight into the putative function(s) of ERb in human breast cancer. A review has recently been published which also deals with the clinical significance of ERb and its isoforms in breast cancer (Saji et al 2005). The current review builds on this by incorporating additional studies and by focusing specifically on ERb, the relationship between clinical ER assays and endocrine therapy outcome, and the likelihood that ERb in addition to ERa may be a clinically useful biomarker of treatment responsiveness in breast cancer.…”
Section: Introductionmentioning
confidence: 99%